EKSPLORASI ETNOMATEMATIKA PADA PROSES MENYADAP POHON KARET DI KECAMATAN TAYAN HILIR - Hedayanti, Meisa; Hartoyo, Agung; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was aimed to explore the activity of ethnomathematics and mathematical concepts in the process of tapping rubber trees in the village of Cingka District Tayan Hilir. In this research, the researcher used descriptive methods and qualitative research. The data was obtained by observations, interviews, and documentation. The subject of this research was four tappers chosen by Purposive Sampling, chosen with specific objectives and considerations. The results showed that there were ethnomathematics activity found that was measuring, calculating, determining location and explaining. The mathematical concept in the process of tapping rubber in the village of Cingka district of Tayan Hilir was the concept of circular circumference, measurement of raw units and not raw, determining the length of time of an incident, ranks and rows, parallel lines, operations Division and multiplication, gradient or slope, measuring weight, parallelogram and there was a concept of geometry also, angles on the tools used in tapping. The mathematical concepts can be used to introduce and understand mathematical concepts through the local cultures, encouraging and enhancing the attractiveness of students to be more motivated in learning mathematics as well as basic in the development of teaching materials. Â Keywords: Exploration, Ethnomathematics, Rubber TappingÂ